PENGARUH KINERJA AKUNTANSI TERHADAP RETURN SAHAM PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2015 - Fitria Nur Aini Wael; Mohammad Amin; Anik Malikah (e_Jurnal Ilmiah Riset Akuntansi, 2017)
ABSTRACTThis study aimed to examine the effect of accounting performance indicatorsare represented by a variable earning per share, price to book value, and priceearnings ratio on stock returns. The sample was Manufacturing Companies includedin the list Indonesia Stock Exchange during the year 2011 up to 2015, Companies arealways consistently submitted their financial statements regularly and havecompleteness of financial data in accordance with what is required in this study,companies that consistently have positive equity value on the observation period isthe year 2011 to 2015. Based on these criteria the sample used in this study is 40companies. The research method was conducted using multiple linear regression, ttest and F. Based on the above results , it can be concluded that the simultaneousearnings per share, price to book value , and price earning ratio has significant effecton stock returns. The results of this study indicate partial earnings per share, price tobook value , and price earning ratio has no significant effect on stock returns .Keywords: EPR (earnings per share) , PBV (price to book value) , PER (priceearnings ratio) , the stock return .